Evaluation of the quality of menus offered to workers by a food service in north of Mato Grosso, Brazil (Research, Society and Development, 2022)
The planning of menus for the community must consider qualitative and quantitative aspects in order to promote a nutritionally balanced diet for diners. The objective of this study was to quantitatively and qualitatively evaluate the menu offered in a food service that provides meals to workers from private companies in the north of Mato Grosso. The restaurant's five-day lunch menus were evaluated in August 2021. The nutritional composition of the menu was compared with the criteria established by the Worker's Food Program (WFP), and the qualitative analysis was performed using the Qualitative Assessment method of Menu Preparations (QAMP). The menu presented an energy value above the parameter established by the program, having a hypoglycemic, hyperproteic and hyperlipidic profile. The amount of sodium present was higher than the recommended daily intake and the fiber supply was adequate on two of the five days evaluated. In the qualitative analysis, the offer of hardwoods and cooking techniques was classified as “excellent”. The presence of sweets, as well as their association with fried foods, and the supply of foods rich in sulfur were classified as “good”. On the other hand, the lack of fruit and monotony of colors were classified as “terrible”, fatty meats were classified as “regular”. The menu analyzed in the food service showed disagreements with the requirements of the PAT, which can affect the health condition of workers, in addition, it is necessary to improve the qualitative characteristics.